Providing Patients with Implantable Cardiac Device Data through a Personal Health Record: A Qualitative Study - Daley, Carly N.; Chen, Elizabeth M.; Roebuck, Amelia E.; Ghahari, Romisa Rohani; Sami, Areej F.; Skaggs, Cayla G.; Carpenter, Maria D.; Mirro, Michael J.; Toscos, Tammy R. (Applied Clinical Informatics, 2017)
Background Patients at risk for sudden cardiac death or having suffered cardiac arrest may receive an implantable cardioverter defibrillator (ICD). This device provides monitoring and therapy for life-threatening heart rhythms. Remote monitoring of ICDs has decreased the time between abnormal heart rhythm events and clinic follow-up. Currently, the data transmitted from the device are reviewed and stored by the clinic, but patients do not have access to the data. While connecting patients directly with their ICD data has potential to enhance engagement in their care and improve health outcomes, patient attitudes and perceptions about receiving ICD data have not been explored.Objective This research is the first demonstration of delivering ICD data to patients through a personal health record (PHR) using a novel technical framework. The objective of this study was to use a PHR interface as a technology probe to explore patients' experiences with directly receiving their ICD data from remote monitoring.Methods We enrolled 21 patients with an ICD undergoing remote monitoring at a large outpatient cardiology clinic in Indiana, United States. Participants received their ICD data from remote monitoring through a PHR over 3 months. In-depth, semistructured interviews were conducted at 3 months and analyzed using thematic analysis.Results Participants were 36 to 86 years old, mean age (SD) of 67 (14) years, predominately male (76%), and white (95%). Key themes were ICD questions and concerns, experiences with remote monitoring, PHR use, and feedback about the ICD data summary. The findings showed that overall, patients desired information that provides reassurance, is easy to understand, and is presented in a meaningful way.Conclusion Sharing ICD data from remote monitoring requires adequate context and scaffolding to support patient understanding. Engaging patients with information that is useful and valuable to them through a PHR may require appropriate and individualized tailoring of information.
Keywords: personal health records; remote monitoring; implantable cardioverter defibrillators; patient engagement; qualitative